(untitled) (Journal of Comparative & International Higher Education, 2022)
In 2019, the U.S. Department of Education (DED) began increasing its enforcement of the Higher Education Act, Section 117 statute, which provides instructions for institutional reporting regarding foreign and contracts. The three questions guiding this article include: What were DED’s stated premises for the investigations? How was international engagement characterized in the notices? And finally, what traits, characteristics, and/or qualities were attributed to different actors? After providing an overview of Section 117, this article examines the notices of investigation issued by DED between 2019 and 2021 to better understand how the Agency discursively characterized malign and/or undue foreign influence utilizing a discourse historical analysis approach. After exploring these questions, this article then discusses the problematic assumptions revealed by four frames which emerged from the notices of investigations and concludes with a brief reflection on the continued challenges for universities and their international engagement (broadly defined) moving forward.